Impact of Slim DC Capacitance on Floating Capacitor H-bridge Motor Drive - Leng, S.; Muyeen, S.M.; Al-Durra, A.; Blaabjerg, F. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2018)
This paper discusses the impact of small dc capacitance in a motor drive using a floating capacitor H-bridge topology. The proposed topology is intended for applications where variable frequency control is not required. Special attention is paid on investigating the second-order dc capacitor voltage ripples, whose influence on the induction motor as well as on the motor drive itself is of importance. This issue is addressed in this paper through rigorous mathematical formulations. It is found that by inverting the second-order dc ripple voltage using the conventional SVPWM, no harmful harmonics will be generated in the motor line voltage. This demonstrates the possibility of drastically reducing the dc capacitance of the proposed system. Induction motor as well as H-bridge performance with respect to different dc capacitance values is demonstrated by experiments, which lays the foundation for cost reduction and reliability enhancement of the proposed system.